Analysis of Difficulty in Solving Story Problems Based on Newman Error Analysis on Flat Building Material in Grade IV Elementary School - Aisah, Tammara Nur; Muiz, Dindin Abdul; W Muharam, Muhammad Rijal (PT. Anagata Sembagi Education, 2024)
This study aims to analyze the difficulties students experience based on errors in solving story problems related to flat shapes using Newman’s Error Analysis procedure. The method used in this research is descriptive analysis. The subjects of the study are fourth-grade students at SDN Sindangkasih. Data was collected through tests and interviews. The results of the data analysis using the Newman procedure reveal that student errors include reading errors at 0.51%, comprehension errors at 2.5%, transformation errors at 16.24%, process skill errors at 39.5%, and encoding errors at 41.63%. The increase in the percentage of errors from reading to encoding is due to students' inability to solve problems correctly after encountering difficulties at the initial stage.